Contemporary Reception of Kate Chopin’s Work in Different Cultures - Irina V. Morozova (Литература двух Америк, 2025)
Kate Chopin Around the World edited by H. Ostman is a collective work of scholars from different countries who share their approaches to studying/teaching the short stories and novels of the American writer. The book consists of three sections, which contain analysis of different approaches to reading and teaching Chopin’s works, comparative studies, and personal perception of the writer’s work. In the first section, “Reading and Teaching Chopin’s Fiction Around the World,” scholars reflect on the experience of studying and/or teaching the American writer’s work in other national contexts. In doing so, the researchers and teachers in this section focus on their personal experiences of encountering Kate Chopin’s work. In the second section, “Comparative Studies of Chopin’s Fiction,” the scholars examine some aspects of the poetics of both well-known and under-researched works by Kate Chopin, and focus on comparing them with the works of women writers from other countries and cultural contexts. The third part is entitled “Reflections” and contains only one chapter, the essay “The Narrative Orchestra in Kate Chopin” by the Italian poet Anna Maria Farabbi, in which she discusses the melodic and poetic language of the American writer.